Clinical Implications of Noncaseating Granulomas on Histology in Patients with Ileal Pouches. Issue 8 (August 2015) - Liu, Ganglei; Ma, Jessica; Liu, Xiuli; Shen, Bo
Abstract : Background: Granulomas are occasionally detected on biopsy specimen of the ileal pouch and their clinical implications are not clear. The aim of this study was to evaluate clinical implications of noncaseating granuloma on histology in patients with ileal pouches. Methods: All eligible patients with confirmed noncaseating granulomas on histology of the biopsy specimens of the pouch body, afferent limb, or cuff in our prospectively maintained Pouch Registry between 2002 and 2014 were evaluated. Demographic and clinical factors were analyzed. The disease course of those patients was evaluated. Results: Of 1564 patients in the Registry, 42 met the criteria and were included. The median duration from the pouch construction to the last visit was 9 years (range, 2–28 yr). Twenty-eight patients (66.7%) developed clinical Crohn's disease (CD) of the pouch, whereas 14 (33.3%) were classified as having histologic CD of the pouch. Six patients (21.4%) in the clinical CD of the pouch group and 4 (28.6%) in the histologic CD of the pouch group had granulomas on more than 1 endoscopy. Postoperative biological therapy was administered more in the clinical CD group than in the histologic CD group (39.3% versus 0%, P = 0.007). Pouch-related fistulae and presacral sinus were verified more in clinical CD group than the histologic CD group. However, Kaplan–Meier plot showed comparable pouch survival between clinical CD and histologic CD groups. Conclusions: In our current study, one-third of the patients with noncaseating pouch granulomas did not develop clinical CD of the pouch. With proper medical therapy, long-term pouch outcomes appeared to be similar in those patients with clinical CD or histologic CD of the pouch. Abstract : Article first published online 2 July 2015